A distributed traffic control scheme based on edge-centric resource management. - Jiang, Yingxin
The correct admission of flows in the Differentiated Services (DiffServ) environment is critical to provide stable and predictable quality of service (QoS) to the end user. Without a scalable and precise admission control scheme, the service provider is faced with either over-provisioning the network or accepting periods of best-effort like behavior. In this paper, we propose a novel approach for admission control that exploits the unique architectural aspects of DiffServ. Through the use of periodic heartbeats emanating from edge routers to probe the network state on the available egress paths, edge routers are able to quickly conduct admission control with a tunable degree of precision. In this paper, we detail our approach, Edge-centric Resource Management (ERM), and conduct detailed simulation studies regarding the effectiveness of the approach.
Keywords: Computer systems organization; Computer communication networks; Network operations; Network monitoring; Algorithms; Measurement